An interdisciplinary approach to study the performance of second - generation genetically modified crops in field trials : a case study with soybean and wheat carrying the sunflower HaHB4 transcription factor - González, Fernanda Gabriela (2020)
Fil: González, Fernanda Gabriela. Instituto Nacional de Tecnología Agropecuaria (INTA). Centro Regional Buenos Aires Norte. Estación Experimental Agropecuaria Pergamino (EEA Pergamino). Pergamino, Buenos Aires, Argentina.